Impacts of UV radiation on respiration, ammonia excretion, and survival of copepods with different feeding habits - Ma, Zengling; Li, Wei; Gao, Kunshan; 高坤山 (SPRINGER, 2013)
Shanghai Municipal Natural Science Foundation [11ZR1449900]; National Natural Science Foundation [40930846, 4112016 4007]; Program for Changjiang Scholars and Innovative Research Team [IRT0941]; China-Japan collaboration project from MOST [S2012GR0290]; State Key Laboratory of Marine Environmental Science, Xiamen University [MELRS0919] Solar ultraviolet radiation (UVR) is known to harm aquatic organisms by damaging key molecules. Here, we showed that UV-A as well as UV-B affected differentially the respiration, ammonia excretion, and mortality of the copepods Pseudodiaptomus marinus (herbivorous) and Labidocera bipinnata (omnivorous). Adding UV-A (320-400 nm, 62.4 W m(-2)) to PAR (400-700 nm, 278 W m(-2)) decreased respiration by 10.2% in P. marinus and 46.1% in L. bipinnata, and additionally, the presence of UV-B (280-320 nm, 2.63 W m(-2)) further decreased it by 8.1 and 18.8%, respectively. The ammonia excretion of P. marinus was suppressed by 13.9% in 30 min exposures to PAR + UV-A compared with those receiving PAR only; however, in the presence of UV-B, it decreased by 13.8% compared to the control. In L. bipinnata, exposure to PAR decreased the ammonia excretion by 33.4%, while the presence of UV-B caused additional suppression by 15.8%. The mortalities of both copepod species increased with prolonged duration under all radiation treatments. More carotenoids and UV-absorbing compounds were found in P. marinus than in L. bipinnata, which could have been responsible for the higher resistance of the former to solar UVR.